Do exerciser weight status and perceived motivation predict instructors’ motivation and beliefs about the exerciser? A test of motivation contagion effects - Ntoumanis, Nikos; Guerrero, M.; Gadeke, C.; Thogersen-Ntoumani, Cecilie (Elsevier BV, 2018)
© 2018 Elsevier Ltd We examined how fitness professionals’ perceptions of a hypothetical exerciser's motivation and weight status impacted the professionals’ motivation to instruct, perceived effectiveness of different interpersonal behaviors toward the exerciser, and beliefs about the exerciser's efficacy to overcome barriers to exercise. Results of a 2 (autonomous vs. controlled exerciser motivation) x 2 (normal weight vs. overweight exerciser) between-subjects experimental design showed that fitness professionals (N = 134) were more autonomously motivated to instruct, perceived autonomy-supportive behaviors as more effective, and had stronger beliefs regarding the exerciser's efficacy when the exerciser was portrayed as having autonomous motivation, compared to controlled motivation. Fitness professionals reported higher levels of controlled motivation to instruct and perceived controlling behaviors as more effective when presented with the overweight exerciser, compared to the normal weight exerciser. Our findings suggest that perceptions of exercisers’ motivation and body weight can influence fitness professionals’ interactions with and beliefs about their clients.